(untitled) (Teología, 2022)
This article proposes guidelines to interpret historically Ealy Christianity, from the first to the beginning of the third Century, in the light of recent work on Popular Culture in the Ancient Mediterranean World. That research perspective tries to put Ealy Christian practices in relationship with cultural perceptions, concrete needs, and expectations of the subaltern groups of the Roman Empire. Ancient Christianity should then be studied mainly by its magical practices, and its popular modes of narrative, who focused on domestic relationships.